Fingerprint image quality measure, feature extraction and matching - Shen, Lin Lin. (2008)
The focus of this research is on image quality determination, features extraction and matching on the fingerprint image. The objective is to develop new techniques or extend on some current published methods so as to improve the overall system reliability. It is desirable to design an automatic scheme that examines and quantifies the quality of an acquired fingerprint image before it is processed. The useful quality information can be combined into the procedure of enhancement, post processing and matching to improve the identification process. A Gabor Feature based method is proposed to estimate the quality of the fingerprint images. By using Gabor Features, our method can offer more accurate estimation of the image quality than the current methods in the literature.